Aspectos introdutórios do capítulo da Medida, conclusão da Doutrina do Ser - Nolasco, Fábio (Revista Eletrônica Estudos Hegelianos, 2017)
ABSTRACT: It was our goal in this presentation to shed some light onto the basic difficulties hindering the approach to the last chapter of Hegel’s Doctrine of Being: Measure. By means of the exposure of [1.] the role of atomism (ancient and modern) in Hegel’s Logic, we approached [2.] some aspects of the Qualität/Quantität relation and introduced in our opinion the key-concept of the Measure-chapter, and perhaps of the whole of the Doctrine of Being: ‘die Wahlverwandtschaften’. This concept is central to the argument of the Measure-chapter because it is the central operator of the passage from ‘reale Maß’ to ‘das Maßlose’ – thereby the ultimate operator of the passage from ‘Measure’ to ‘Essence’. We ilustrated this concept through the presentation of three ‘figures’ of ‘Wahlverwandtschaften’, i.e. the three thought-objects, which ‘atomistic representation’ tries to conceive in quantitative terms, and which ‘speculative thinking’ treats conceptually, that is: in terms of quality: [3.] musical tones, [4.] chemical elements and [5.] infinitesimals. Thus we claim that the observation of these figures leads the way for the comprehension that Hegel, in the passage from Measure to Essence, brings to light a certain logische Aufhebung of the modern, quantitative notion of scientific law – and of ‘modern quantitative ontology’ as a whole.